The spectrum of myopathies in the city of São Paulo - José A. Levy; Abram Topczewski; Lucia Iracema Z. de Mendonça; Mayana Zatz; Ruth Blay Levisky (Arquivos de Neuro-Psiquiatria)
A review of all myopathic patients treated at the Neurologic Clinic of the Medical School of the University of São Paulo during the past 15 years is reported. A total of 466 cases were examined and distributed as follows: 56% of progressive muscular dystrophy; 31% of myasthenia gravis; 6% of polymyositis; 4% of myotonic dystrophy; and the remainder of several different diseases (central core disease, Kearns-syndrome, myotonia congenita, adynamia episodica hereditaria, diabetic myopathy and Eaton-Lambert syndrome). Enzymatic dosages, electromyography, muscle biopsy, electrocardiography and genetic counselling are also reported.